Lecturer’s perception on English proficiency among UITM students in campus Samarahan I & II / Shafflene Samen and Commorie Jati Richard - Samen, Shafflene; Richard, Commorie Jati (2014)
The study conducted is about lecturer’s perception on English proficiency among students in University Technology MARA Sarawak Campus Samarahan I and II. The research is focused on the perception of lecturers from the Academy of Language Study (APB) towards the English language proficiency among the diploma students from the Social Sciences and Humanities Cluster, Science and Technology Cluster and Management and Business Cluster. This chapter will discuss on the background of the research, problem statement and scope of study. It then continues to identify the research objectives, the significance of the study and the research issues involved in the topic under this study.